Synthesis and Studies of Anticancer and Antimicrobial Activity of New Phenylurenyl Chalcone Derivatives - Akdeniz, Güneş Y.; Akgün, Hülya; Özakpınar, Özlem B.; Duracık, Merve; Öztürk, Mehmet; İşcan, Evin and Başoğlu, Faika (Letters in Drug Design & Discovery, 2022)
Background: Phenylurenyl chalcone structures have the potential to act as a scaffold in anticancer drug discovery. Methods: N-Phenethyl-N'-4-[(2E)-3-phenylprop-2-enoyl]phenylurea, 4/3-[(2E)-3-substitutedphenylprop-2- enoyl]phenyl-N-phenylurea,4/3-[(2E)-3-substitutedphenyl. prop-2-enoyl]phenyl-N-methylphenyl urea and 4/3-[(2E)-3-substitutedphenylprop-2-enoyl]phenyl-Nethylphenyl urea derivatives(1-35) were prepared and evaluated for their anticancer and antimicrobial activity against A-549 Hep-3B, HT-29, CF-7, PC-3, K-562 NIH-3T3 and Huh-7 cell lines and against Staphylococcus aureus (ATCC 6538), Pseudomonas aeruginosa (ATCC 9027), Escherichia coli (ATCC 8739) and Candida albicans (ATCC 10231), respectively. Results: While compounds 2, 26, 29, and 34 showed moderate cytotoxic activity on cell line Huh 7, compounds 14 (IC50: 6.42 μM), 16 (IC50: 5.64 μM), 19 (IC50: 6.95 μM) and 34 (IC50: 6.87 μM) showed good cytotoxic activity on Huh-7 cell line close to Sorafenib (IC50: 4.29 μM) (as reference). MIC values of compounds 4 and 22 against E. coli were 25 μg/ml, compounds 3, 14 and 29 against P. aeruginosa 25 μg/ml, and compounds 11 and 33 against S. aureus 25 μg/ml. On the other hand, the minimum inhibitory concentration of all tested compounds against C. albicans was 25 μg/ml. Conclusion: N-Phenethyl-N'-4-[(2E)-3-phenylprop-2-enoyl]phenylurea may be a new candidate to be developed as an anticancer compound.
Keywords: cytotoxicity